Shipping to Heterogeneous Customers with Competing Carriers - Lu, Tao; Chen, Ying-Ju; Fransoo, Jan C.; Lee, Chung-Yee (Manufacturing and Service Operations Management, 2020)
Problem definition: We study a shipper transporting and selling a short life-cycle product to a destination market via two competing transportation service providers (i.e., carriers). The two carriers offer distinct speeds and competing freight rates, whereas customers in the destination market obtain higher utility if they receive the product earlier and their time preferences are heterogeneous. Academic/practical relevance: Perishable products are commonly shipped via multiple means of transport. The faster the mode of transport, the more expensive it is, but speed enables the product to reach the market with higher quality. In addition to the trade-off between speed and cost, the competition between carriers can also influence the shipper's transportation procurement strategies. Our model highlights the implications of carrier competition in a dual sourcing problem. Methodology: We analyze a two-stage game in which carriers first compete on freight rates, and then the shipper determines the shipping quantities. Results: We show that the shipper may benefit from product differentiation via dual-mode shipping, in which the shipment that arrives earlier is sold at a premium price. In equilibrium, the shipper's profit can be U-shaped in the speed difference between carriers. Dual sourcing may be inferior to simply restricting a single shipping service in a winner-take-all fashion. Managerial implications: This study reveals an underlying trade-off between the operational advantage from product differentiation and the cost advantage from carrier competition. To benefit from either of these advantages, a shipper should use two carriers with either very distinct or very similar speeds. Single sourcing may bring an additional cost advantage that outweighs the value of production differentiation through dual sourcing.